Steel softer than silk: gender roles and the disguised maiden in fairy tales - Ramos, Samira dos Santos (Literartes, 2020)
The paper is a comparative study about the maiden disguised in Portuguese and Brazilian fairy tales. Considering the results, the displacement of gender roles was part of fairy tales of before the visibility of Gender Studies in contemporary times.